2014
DOI: 10.1002/chem.201402610
|View full text |Cite
|
Sign up to set email alerts
|

Configuration‐ and Conformation‐Dependent Electronic‐Structure Variations in 1,4‐Disubstituted Cyclohexanes Enabled by a Carbon‐to‐Silicon Exchange

Abstract: Cyclohexane, with its well-defined conformers, could be an ideal force-controlled molecular switch if it were to display substantial differences in electronic and optical properties between its conformers. We utilize σ conjugation in heavier analogues of cyclohexanes (i.e. cyclohexasilanes) and show that 1,4-disubstituted cyclohexasilanes display configuration- and conformation-dependent variations in these properties. Cis- and trans-1,4-bis(trimethylsilylethynyl)cyclohexasilanes display a 0.11 V difference in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…Emanuelsson et al . studied the relationship between conformational effects and conductance of 1,4‐disubstituted cyclohexasilanes anchored with thiophenyl groups (Figure ) . Conductance measurements using the aforementioned STM‐break junction technique revealed that the trans‐ conformer with both the substituents in equatorial positions (Figure , right) was more conducting than the trans‐ conformer with both the substituents in axial positions (Figure , left).…”
Section: Unique σ‐Conjugated Bonds In Polysilanesmentioning
confidence: 99%
“…Emanuelsson et al . studied the relationship between conformational effects and conductance of 1,4‐disubstituted cyclohexasilanes anchored with thiophenyl groups (Figure ) . Conductance measurements using the aforementioned STM‐break junction technique revealed that the trans‐ conformer with both the substituents in equatorial positions (Figure , right) was more conducting than the trans‐ conformer with both the substituents in axial positions (Figure , left).…”
Section: Unique σ‐Conjugated Bonds In Polysilanesmentioning
confidence: 99%
“…The shift in the formal potential of 480 mV is significantly higherc ompared with other conformation-dependents tructures such as cis-trans cyclohexasilanes (110 mV). [21] This vast formal potentiald rop in our peptides provides two distinct states (i.e.,o n/off)w ith as izeable differential, which is ideal for the design of molecular switches. Defining the electron transfer pathway in peptides attached to am onolayer (electrode) is crucial to the design of singlemolecule junction devices.…”
Section: Electrochemical Analysis Of Intramolecular Electron Transfermentioning
confidence: 99%
“…This probably resulted from the impact of the c/d-ring conformational change upon formation of the C-14/C-15 double bond, as evidenced previously. 34 When evaluated toward the HT-29 cell line, 30 5b and 5d were cytotoxic, but 5c, 5e , and 5f were all inactive in this regard (Table 5). …”
Section: Resultsmentioning
confidence: 99%